Synthesis, Characterization and Bioactivity Study of Cyclic Diesters of 4,4'-Cyclohexylidene Bisphenol - Jayamani, V.; Prathipa, C. (Asian Journal of Chemistry, 2010)
Macrocycles 4,4'-cyclohexylidene bisphenyl butan-1,4-dioate,4,4'-cyclohexylidene bisphenyl hexan-1,6-dioate and 4,4'-cyclohexylidene-bisphenyldecan-1,10-dioate have been synthesized by ring closure using high dilution technique. Structures are characterized by physical, analytical and infrared, 1H , 13C NMR and mass spectral data. Compounds showed positive inhibition against gram positive bacteria Staphylococcus aurous.